A MULTIDIMENSIONAL SUBDIFFUSION MODEL WITH CHEMOTAXIS - Guswanto, Bambang Hendriya (Universitas Jenderal Soedirman, 2019)
ABSTRACT. The mathematical model for subdiffusion process with chemotaxis proposed by Langlands and Henry [1] for the one-dimensional case is extended to the multi-dimensional case. The model is derived from random walks process using a probability measure on a n-multidimensional unit ball S^(n-1).Keywords: multi-dimensional model, subdiffusion, chemotaxis. ABSTRAK. Model matematika untuk proses subdifusi dengan kemotaksis yang diturunkan oleh Langlands dan Henry [1] untuk kasus satu dimensi diperluas ke kasus multidimensi. Model ini diturunkan dari proses gerak acak dengan menggunakan ukuran peluang pada bola satuan multidimensi-n S^(n-1).Kata kunci: model multidimensi, subdifusi, kemotaksis.